Quebec's Comprehensive Auto No-Fault Scheme and the Failure of Any of the United States to Follow - Sugarman, Stephen (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1998)
Although Quebec's no-fault auto insurance scheme has served for 20 years as an exemplary model to follow, so far not one of the United States has adopted anything even close to it. This article examines the reasons for that failure, both in California and throughout the country. Emphasis is given to several factors that stand in the way of U.S. reform and that may distinguish states in the U.S. from Canadian provinces generally and Quebec in particular: 1. State politics — the power of the lawyers who represent victims, the position of the insurers, and the structure of state government. 2. Public perceptions — negative attitudes towards government, the insurance industry, and the prospects of saving money on auto insurance premiums. 3. Traditions—the ideological strength of individualism and ideological weakness of collective responsibility. 4. Tradeoffs — doing away with the tort system means giving up more in the U.S. than elsewhere. 5. Policy concerns — fears about safety, costs, and the « slippery slope ». Finally, the possibility that one or more U.S. states might in the future evolve towards the Quebec solution is explored.